2014
DOI: 10.2106/jbjs.m.00199
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Three-Dimensional CT Imaging on Intraobserver and Interobserver Reliability of Proximal Humeral Fracture Classifications and Treatment Recommendations

Abstract: Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…Extensive effort has been made to improve reliability, including training [3,15], different imaging modalities [2,[16][17][18][19][20]23], and simplifying classification systems [2,24]. Our findings show that the interobserver reliability for the recognition of tibial plateau fracture characteristics on CT scans is higher on MPEG4 videos compared to that on DICOM viewer.…”
Section: Discussionmentioning
confidence: 79%
“…Extensive effort has been made to improve reliability, including training [3,15], different imaging modalities [2,[16][17][18][19][20]23], and simplifying classification systems [2,24]. Our findings show that the interobserver reliability for the recognition of tibial plateau fracture characteristics on CT scans is higher on MPEG4 videos compared to that on DICOM viewer.…”
Section: Discussionmentioning
confidence: 79%
“…Unfortunately, the majority of the studies that explored the opportunity of using CT scans to improve agreement in classification reported no significant results [27,30]. Other authors have reported that the use of 3D-CT scans does not improve the reliability of either the Neer or AO/ OTA classification over traditional CT [31,32]. Given that advanced imaging modalities have not been shown to improve interobserver agreement, we compared the three classification systems using only x-rays.…”
Section: Discussionmentioning
confidence: 98%
“…Assessment of the fracture pattern was independently conducted by a total of 6 orthopedic surgeons, including 3 shoulder surgeons (observers 1–3) and 3 orthopedic trainees, who were young surgeons with less than 4 years of experience as orthopedic surgeons (observers 4–6). The examiners categorized the fractures into 1-part (minimal displacement), 2-part, 3-part, and 4-part fractures by the number of fracture fragments involved, [ 11 , 21 ] but subcategorization of fractures was not assessed in this study. The cases were grouped according to the conventional Neer classification (conventional method) using plain radiographs, and then the CT scans for each case were assessed by each examiner.…”
Section: Methodsmentioning
confidence: 99%
“…Advances in computed tomography (CT) imaging technology have facilitated determining whether fractures have occurred and understanding how the fracture is displaced, and CT is now used frequently to evaluate proximal humeral fractures [ 16 , 17 ]. However, its reproducibility remains in doubt even with the use of CT scans and 3-dimensional computational CT reconstructions [ 14 , 18 21 ].…”
Section: Introductionmentioning
confidence: 99%